DAMPAK PENGHAPUSAN PENCATATAN PERUSAHAAN TERBUKA TERHADAP PEMEGANG SAHAM DAN TATA KELOLA PERUSAHAAN - Purba, Anita Sara (Ensiklopedia Education Review, 2025)
Abstract: This study aims to discuss two problem formulations, namely: (1) how legal regulations in Indonesia regulate the cancellation of delisting of public companies and its impact on shareholder protection, and (2) what are the implications of delisting on the principles of good corporate governance. This study uses a normative legal approach method, by examining laws and regulations, legal literature, and relevant official documents. The results of the study indicate that the regulations of the Financial Services Authority and the Indonesia Stock Exchange do provide a legal framework for the implementation of delisting, including the obligation to tender offer for minority shareholders, but there are still gaps in the protection provided, especially in non-voluntary delisting. In addition, the delisting process can also disrupt the implementation of the principles of transparency, accountability, and fairness in corporate governance. Therefore, strengthening regulations and supervision is needed to ensure that the delisting process is carried out while still guaranteeing the rights of shareholders and maintaining the governance standards that have been applied during the company's public status.Keywords: Corporate Governance, Impact, Shareholders.